Social and behavioral factors influencing e-waste recycling practices in Malaysia - Omar, Mawardi; Samsudin, Norshuhada; Ahmad Shukri, Fuziatul Norsyiha; Syed Abdullah, Sharifah Sarimah (Unit Penerbitan JSKM, 2025)
Electronic waste (e-waste) is a rapidly growing environmental challenge in Malaysia, driven by digitalization, rising incomes, and shorter product lifecycles. Despite established recycling infrastructure, formal collection rates remain low. This conceptual paper explores the social and behavioral factors influencing e-waste recycling participation, drawing on existing literature. Social determinants include cultural norms, peer influence, community engagement, public education, and socioeconomic status, which shape collective attitudes toward recycling. Behavioral factors, such as individual attitudes, habits, perceived convenience, trust in recycling systems, awareness, and economic incentives, directly affect participation rates. These influences operate interactively, highlighting the need for integrated strategies that combine accessible infrastructure, targeted education, incentive schemes, and community norm-building. The paper proposes a conceptual model to guide future research and policymaking, with the aim of bridging the gap between policy targets and actual recycling behavior, contributing to Malaysia’s transition toward sustainable e-waste management.